PENGARUH CAPITAL INTENSITY, CORPORATE SOCIAL RESPONSIBILITY, DAN CORPORATE GOVERNANCE TERHADAP AGRESIVITAS PAJAK - NURUS SAKINAH (2020)
This study aims to determine the effect of capital intensity, corporate social responsibility, and corporate governance on tax aggressiveness. In this study tax avoidance is proxied using Book Tax Differences (BTD). The sample used innthis study were 64 manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2018. The analysis technique used in this study is panel data regression analysis with a significance level of 5%. The results in this study found that (1) capital intensity had no effect on tax aggressiveness. (2) corporate social responsibility had no effect on tax aggressiveness. (3) corporate governance has a significant negative effect on tax aggressiveness, because if more and more sample companies are audited by KAP the Big Four, the lower the tax avoidance that will occur. Keywords: Capital Intensity, Corporate Social Responsibility, Corporate Governance, Tax Aggressiveness.